Hypoxic preconditioning improves the survival and neural effects of transplanted mesenchymal stem cells via CXCL12/CXCR4 signalling in a rat model of cerebral infarction. (31st July 2019) - Hu, Yueqiang; Chen, Wei; Wu, Lin; Jiang, Lingfei; Qin, Hongling; Tang, Nong
Abstract : The treatment of neural deficiency after cerebral infarction is challenging, with limited therapeutic options. The transplantation of mesenchymal stem cells (MSCs) to the ischemic penumbra is a potential therapeutic approach. In the present study, a cerebral infarction model was generated by performing middle cerebral artery occlusion (MCAO) in SD rats. The expression of CXCR4 increased, and the number of MSCs migrating to the peri‐infarct area was higher in rats transplanted with preconditioned MSCs than in rats transplanted with untreated MSCs. The rate of apoptosis, as evaluated by TUNEL staining and immunoblotting assays, was reduced in rats receiving preconditioned MSCs. A significant amelioration of neural regeneration and improved neurological function were observed in rats injected with preconditioned MSCs compared with those injected with untreated MSCs. However, the application of an siRNA targeting CXCL12 significantly inhibited the protective role of preconditioned MSCs against apoptosis and promoted the migration of MSCs to the ischemic area, leading to impaired neuronal regeneration and limited recovery of neuronal function. Hypoxic preconditioning of MSCs prior to transplantation suppressed apoptosis and increased their migration abilities, leading to the promotion of neuronal regeneration and improvement in neural function after transplantation. This preconditioning strategy may be considered as a potential approach for the modification of MSCs prior to cell transplantation therapy in patients with cerebral infarction. Significance of the Study: We found that hypoxic preconditioning of MSCs improved their ability to promote neuronal regeneration and the recovery of neuronal function. Moreover, we showed that CXCR4 inhibited apoptosis, improved cell homing, and promoted neuronal differentiation, without influencing angiogenesis. Our study provides a relatively safe preconditioning method for potential use for cell transplantation therapy in ischemic cerebral infarction. The results presented here will facilitate the development of novel strategies and techniques to improve the tolerance and migration ability of transplanted cells for the treatment of cerebral infarction sequelae.